Pengaruh salat tahajjud terhadap tingkat stres mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Farah Dea Annisa; Maulana Siregar (Journal of Health and Therapy, 2026)
Stress is a common problem among students, especially medical students, who face high academic pressure. This study aims to determine the relationship between performing tahajjud prayers and stress levels among students at the Faculty of Medicine, University of Muhammadiyah Sumatera Utara. The research method used was an analytic-descriptive, cross-sectional design involving 73 respondents selected through accidental sampling. Data were collected using the DASS-21 questionnaire to measure stress levels and an additional questionnaire regarding the frequency of tahajjud prayer. Data analysis was performed using univariate and bivariate analyses with the chi-square test. The results showed that 52.1% of respondents often performed the tahajjud prayer, and 34.2% experienced stress. Statistical tests showed a significant relationship between the frequency of tahajjud prayer and stress levels. In conclusion, the more often students perform the tahajjud prayer, the lower their stress levels tend to be.